Motivation in Physical Education class according to sex, age, level of physical activity and adherence to the Mediterranean diet - Gascón Colorado, Jorge; Maneiro Dios, Rubén; Garrote Jurado, Ramón; Moral García, José Enrique (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The objective of this study was to analyze students’ motivation toward physical education (PE) classes and to examine how this motivation is associated with sex, age, level of physical activity, and adherence to the Mediterranean diet among schoolchildren. The sample consisted of 564 students between the ages of 10 and 13, of whom 53.2% were boys and 46.8% were girls. To gather data, several instruments were administered, including a sociodemographic questionnaire, the Physical Education Class Motivation Questionnaire, the International Physical Activity Questionnaire for Adolescents (IPAQ-A), and the KIDMED index, which assesses adherence to the Mediterranean diet. The findings revealed a generally high level of satisfaction with PE classes among participants. Furthermore, boys reported higher levels of motivation compared to girls. Students with medium adherence to the Mediterranean diet demonstrated greater intrinsic motivation, suggesting that healthier dietary patterns may be linked to internal drivers for participation in physical activity. Additionally, students who reported being very physically active showed higher levels of extrinsic motivation, indicating that external factors may play a role in encouraging participation in physical activity among this group.